(untitled) (Scientific journal of the Fergana State University, 2025)
This article explores the unique features of speech etiquette in German and Uzbek families. The study reveals that German families emphasize personal independence, straightforwardness, and time appreciation, while Uzbek families prioritize respect, unity, and social values. Linguistic and cultural characteristics were analyzed based on Hofstede’s cultural dimensions theory. The findings contribute to a deeper understanding of intercultural communication.